Elaboração e descrição de situações didáticas com amparo na sequência Fedathi: o caso da integral imprópria - Nasserala, Alessandro Mendonça (2014)
This research developed and described didactic situations on Improper integrals or generalized, supported the Fedathi sequence that we use as teaching methodology and the Didactic Engineering as a research methodology. Note that this only employ two phases (preliminary analysis and a posteriori analysis) comprehensively. In addition to using GeoGebra software as a tool to develop and report didactic situations, we also content analysis from the perspective of Bardin (1977, 2009) of books Guidorizzi (1998) and Stewart (2011) on Improper integrals. Being a professional master produced as an educational product, video classes and a blog to disseminate materials on Improper integrals. This research pointed out that the teaching and learning of the Improper integral may have as an ally to new technologies, using the dynamic geometry without losing the mathematical rigor, and that students of higher institutions, especially those with the Calculus II as a discipline in some courses as Mathematics and Engineering can earn in methodologies and teaching and learning tools, with that we would have an improvement in the teaching of the discipline of Calculus II, in particular the content of the Improper integral.